Implementasi hukum ekonomi syariah dalam praktik bisnis modern di indonesia - Siroj, Amin Muhammad (Maliki Interdisciplinary Journal, 2025)
The implementation of islamic economic law in Indonesia has significantly progressed, particularly in the financial sector, real sector, and corporate social responsibility (CSR). Principles of justice, transparency, and sustainability serve as the foundation of Sharia-based business practices. However, various challenges. remain, including a lack of understanding of Islamic economic law, limited human resources, and competition with conventional products. Proposed solutions include improving human resource quality, developing innovative products, fostering collaboration among stakeholders, and educating the public. These strategic steps aim to enhance the role of islamic economics in national economic growth and societal well-being.